A vanadium dioxide-based metamaterial with quatrefoil and circle loaded structure on flexible polyamide substrate for terahertz applications - Abdulkarim, Yadgar I.; Awl, Halgurd N.; Muhammadsharif, Fahmi F.; Bakır, Mehmet; Alkurt, Fatih Özkan; Altıntaş, Olcay; Saeed, Salah Raza; Taouzari, Mohamed; Karaaslan, Muharrem; Appasani, Bhargav; Dong, Jian (Frontiers in Physics, 2022)
In this study, a novel broadband metamaterial (MTM) absorber is proposed, which is based on vanadium dioxide (VO2) resonators coated onto a flexible polyamide substrate. The VO2 resonator is in the form of a quatrefoil and circle-loaded complementary square split ring resonator (CSSRR), which is fine tuned to operate in the terahertz range. The MTM design and simulation were carried out using Computer Simulation Technology (CST) software, by which different layouts were investigated achieve the optimum structure. The results showed the presence of two pronounced peaks for the proposed MTM structure at 0.88 and 1.42 THz. The absorption peaks were found to be insensitive to the wave polarization and incident angle from 00 to 900. The absorption mechanism of the MTM was investigated considering the insulating and metallic states of VO2. The results were in good agreement with those calculated using high frequency simulated structure (HFSS) software. The flexible nature of the proposed MTM design makes it a viable candidate for non-planar and conformal geometry applications in stealth technology, and terahertz imaging.